ANALISA LAPORAN KEUANGAN PT. WIJAYA KARYA (PERSERO) TBK PADA TAHUN 2020 - Novita Nur Rahmawati; Muhani - (AKRUAL : Jurnal Akuntansi dan Keuangan, 2022)
Purpose Financial reports are needed by those who invest their capital so that they need information about the smooth activities and profitability of the company in detail and transparently on potential dividends, because with this information, shareholders can decide to retain their shares. On November 25, 2016, all of the Company's shares issued through a limited public offering totaling 2,820,726,372 shares were listed on the Indonesia Stock Exchange (IDX). Financial statement analysis is one of the indicators for assessing and knowing the company's performance and maximizing the upcoming work period. Apart from being an indicator.